PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII MTsN 1 KOTA PADANG - Maharani, Bella Zahra (Jurnal Edukasi dan Penelitian Matematika, 2023)
Abstract – Learners need to have strong communication skills in mathematics. The pupils in class VIII MTsN 1 in Padang City exhibited poor mathematics communication abilities throughout the academic year 2023/2024. This was shown by the mathematical communication exam that they took. This technique of learning via duo work may be helpful in enhancing these mathematical communication abilities. This study makes use of a pseudo experiment using a static group design for its methodology. We utilised a straightforward random sampling method. Class VIII.1 serves as the experimental group, while class VIII.5 serves as the control. When compared to pupils who had received their education via direct learning, those who had participated in cooperative learning through the type pair check model demonstrated significant improvement in their mathematics communication abilities (P-Value = 0.000 = 0.05).Keywords. – Mathematical Communication Abilities, Pair Check